PENGARUH PENDAPATAN ASLI DAERAH DAN DANA PERIMBANGAN TERHADAP PERTUMBUHAN EKONOMI PADA PEMERINTAH KABUPATEN/KOTA DI JAWA TENGAH - Bambang Widarno, Dwi Handayani, Rispantyo & (Universitas Slamet Riyadi, 2017)
The implementation of regional autonomy demands of each local governmentto independently finance the expenditure areas, as indicated by increased economicgrowth. The purpose of this study were: to analyze the significance of the influence ofregional revenue and Fund Balance partially or simultaneously to Economic Growthin Regency / City in Central Java. This study uses a case study in the District / Cityin Central Java for 2013-2015, the type of data used quantitative and qualitativedata, the data source used secondary data. The samples are all regencies / cities inCentral Java province a total of 35 districts / cities, so this study is a census study.Data analysis techniques used classical assumption test and multiple linearregression analysis, t-test, F and coefficient of determination. In conclusion, thatthere is a positive and significant influence local revenues to economic growth in theDistrict / City in Central Java, meaning that if the local revenue increases it canincrease economic growth. There is a positive and significant impact on economicgrowth of equalization funds in the District / City in Central Java, meaning that if thebalancing fund increases it can increase economic growth. There is significantinfluence local revenues and equalization funds simultaneously on the dependentvariable is economic growth in the District / City in Central Java.Keywords: local revenues, equalization funds, economic growth.